Binge alcohol use is not associated with alterations in striatal dopamine receptor binding or dopamine release. (1st December 2019) - Wai, Jonathan M.; Grassetti, Alexander; Slifstein, Mark; Matuskey, David; Nabulsi, Nabeel; Ropchan, Jim; Labaree, David; Huang, Yiyun; Martinez, Diana
Highlights: Little is known about dopaminergic brain changes associated with binge drinking. Binge drinking was not associated with changes in D2/3 binding. Binge drinking was not associated with changes in stimulant-induced DA release. Patterns of alcohol use were also not associated with changes in brain dopamine. Abstract: Background: Previous imaging studies using Positron Emission Tomography (PET) have shown that alcohol use disorder (AUD) is associated with a decrease in dopamine type 2/3 receptor (D2/3 ) binding and dopamine transmission. Although binge drinking is a risk factor for future AUD, little is known about the neurobiology of binge drinking in young adults. This study measured D2/3 receptor binding and stimulant-induced dopamine release using PET and [ 11 C]raclopride in binge drinkers without an AUD. Methods: This study included 14 healthy controls (HC) and 14 young adult binge drinkers (BD), aged 18-25. The BD met National Institute on Alcohol Abuse and Alcoholism (NIAAA) criteria for binge drinking and the HC subjects were social drinkers. The subjects were scanned with [ 11 C]raclopride before and after the administration of oral methylphenidate (60 mg) to measure D2/3 binding and dopamine release. Results: There was no significant difference in the PET measures of D2/3 binding or methylphenidate-induced dopamine release between the two groups. There was no significant association between Alcohol Use Disorders Identification Test (AUDIT) scores or 30-day drinking history and the imaging data. Conclusion: In this sample of 18–25-year-old binge drinkers without a diagnosis of a substance use disorder, there were no significant differences in D2/3 receptor binding potential or methylphenidate-induced dopamine release relative to healthy controls.